IDNLearn.com: Your go-to resource for finding expert answers. Whether your question is simple or complex, our community is here to provide detailed and trustworthy answers quickly and effectively.
Sagot :
Answer:
(x+3)²+(y+5)² = 36
Step-by-step explanation:
The general equation of a circle is expressed as;
(x-a)²+(y-b)² = r² where;
(a, b) is the centre of the circle
r is the radius of the circle
Given
Centre (-3, -5)
a = -3 and b = -5
radius r = 6units
Substitute
(x-a)²+(y-b)² = r²
(x-(-3))²+(y-(-5))² = 6²
(x+3)²+(y+5)² = 36
hence the required equation is (x+3)²+(y+5)² = 36
The equation of a circle that represents a circle with a center at (-3, -5) and a radius of 6 unit is (x + 3)² + (y + 5)² = 36
Equation of a circle
The general equation of a circle is expressed as follows:
(x-a)²+(y-b)² = r²
where
- r = radius of the circle
- a and b are the centre of the circle
Therefore,
a = -3
b = -5
r = 6
Hence,
(x - (-3))² + (y - (-5))² = 6²
(x + 3)² + (y + 5)² = 36
learn more on circle here: https://brainly.com/question/22718701
#SPJ5
Your participation is crucial to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.